Comparative Analysis of Antithrombotic Therapy in In-Patients with Atrial Fibrillation - V. I. Petrov; O. V. Shatalova; A. S. Gerasimenko; V. S. Gorbatenko (Столичная издательская компания, 2019)
Aim. To study the frequency of prescribing antithrombotic agents in patients with non-valvular atrial fibrillation (AF) who were hospitalized in the cardiology department of a multidisciplinary hospital.Material and methods. A retrospective one-time study of medical records of 765 patients with non-valvular AF treated in the cardiology department of a multidisciplinary hospital in 2012 and 2016 was performed.Results. All patients were stratified in three groups depending on the CHA2DS2-VASc score. The frequency of prescribing antithrombotic agents was evaluated in each group. A low risk of thromboembolic complications was found in 1% (n=3) of patients in 2012 and 0.6% (n=3) in 2016. All these patients received antithrombotic agents. CHA2DS2-VASc=1 was found in 6% (n=15) of patients with AF in 2012 and in 3.4% (n=17) in 2016. A significant number of patients in this group received anticoagulant therapy with vitamin K antagonists (warfarin) or with direct oral anticoagulants. A high risk of thromboembolic complications (CHA2DS2-VASc≥2) was found in 93% of patient (n=245) in 2012 and in 96% (n=482) in 2016. Anticoagulant therapy was prescribed in 70.2% (n=172) patients with high risk in 2012 and 80% (n=387) in 2016. However, some patients with high risk of thromboembolic complications did not have the necessary therapy.Conclusion. Positive changes in the structure and frequency of prescribing anticoagulant drugs in patients with AF and a high risk of thromboembolic complications were found during the years studied.